The Dissident Interview: A Deterritorializing Guerrilla Encounter. (July 2020) - Barlott, Tim; Shevellar, Lynda; Turpin, Merrill; Setchell, Jenny
Drawing from the work of Deleuze and Guattari, we experimentally chart a cartography of a peculiar interview (an "off-topic" and "dissident" interview that disrupts the agenda of the interviewer). In this article, we aim to traverse the micropolitics of the interview, the entangled relations of power and resistance. We intentionally chart the intensive topography of the peculiar and re-present what was once missed (or passed over). Thinking with theory rather than method, we have used Deleuze and Guattari's conceptualization of social machines, deterritorialization, and desire, to interrogate and experiment with the dissident interview. Performed as a nine-movement guerrilla encounter, the peculiarities of the interview are re-presented as unconventional guerrilla tactics that deterritorialize and disrupt the interview. Our experimentation surfaced some of the ways an interview can be despotic, stifling affective production. However, a Deleuzio-Guattarian war machine prevented the capture and appropriation of the interview and produced a new creative machine.